Application of Runoff Confluence Model in Early Warning of Mountain Floods in Small Watersheds of Sichuan - YE Bangping; DING Yuhong; LIU Jinbao; CHEN Jun; ZHANG Xiaoli (Renmin Zhujiang)
Taking a small watershed in the Pengzhou mountainous area of Sichuan as the research object,this paper employs historical precipitation data,watershed zoning data,DEM,and other data to calibrate the model parameters on a watershed runoff confluence model based on Navier-Stokes equation (N-S equation) with stable flow fields.The conclusions are as follows:① After model parameter calibration,the diffusion coefficient is 0.12,with an acceleration coefficient of 0.12 and a maximum water velocity of 3;② The analysis of confluence characteristics under different precipitation scenarios shows that with the increasing rainfall,the maximum water depth rises,and the time for maximum increase in water depth and the time for the maximum water depth decrease.The watersheds with the maximum time for a water depth of less than 200 min are mainly the upper watersheds,while those with the maximum time for a water depth of more than 200 min are mainly the main watersheds;③ The assessment reveals that there are no watersheds with high risk levels of mountain floods in the small watershed of Pengzhou mountainous area,17 watersheds with high levels,19 watersheds with relatively high levels,and only one watershed with low levels.